Behavior of Partially Saturated Cohesive Soil under Strip Footing - Mohammed Yousif Fattah; Mahmood Diab Ahmed; Hadeel Ammar Mohammed (Journal of Engineering, 2023)
In this paper, a shallow foundation (strip footing), 1 m in width is assumed to be constructed on fully saturated and partially saturated Iraqi soils, and analyzed by finite element method. A procedure is proposed to define the H – modulus function from the soil water characteristic curve which is measured by the filter paper method. Fitting methods are applied through the program (SoilVision). Then, the soil water characteristic curve is converted to relation correlating the void ratio and matric suction. The slope of the latter relation can be used to define the H – modulus function. The finite element programs SIGMA/W and SEEP/W are then used in the analysis. Eight nodded isoparametric quadrilateral elements are used for modeling both the soil skeleton and pore water pressure. A parametric study was carried out and different parameters were changed to study their effects on the behavior of partially saturated soil. These parameters include the degree of saturation of the soil (S) and depth of water table. The study reveals that when the soil becomes partially saturated by dropping water table at different depths with different degrees of saturation, the bearing capacity of shallow foundation increases about (4 – 7) times higher than the bearing capacity of the same soil under saturated conditions. This result is attributed to matric suction value (i.e negative pore water pressure). The behavior of soil in partially saturated condition is like that of fully saturated condition but with smaller values of displacement. It is found that the settlement is reduced when the water table drops to a depth of 2 m (i.e. twice the foundation width) by about (92 %).